Obesity paradox among elderly patients with coronary artery disease undergoing non-cardiac surgery - Che, Lu (J Geriatr Cardiol, 2018)
BACKGROUND: High body mass index (BMI) is a risk factor for chronic cardiac disease. However, mounting evidence supports that high BMI is associated with less risk of cardiac morbidity and mortality compared with normal BMI, also known as the obesity paradox. Therefore, we sought to determine the existence of the obesity paradox in regard to perioperative 30-day cardiac events among elderly Chinese patients with known coronary artery disease undergoing non-cardiac surgery. METHODS: A post-hoc analysis of a prospective, multi-institutional cohort study was performed. Patients aged > 60 years with a history of coronary artery disease and undergoing non-cardiac surgery were grouped according to BMI: underweight (< 18.5 kg/m(2)), normal weight (18.5–24.9 kg/m(2)), overweight (25–29.9 kg/m(2)) and obese (≥ 30 kg/m(2)). Demographic information, perioperative clinical variables and incidence of 30-day postoperative cardiac adverse event were retrieved from a research database. RESULTS: We identified 1202 eligible patients (BMI: 24.3 ± 3.8 kg/m(2)). Across BMI groups, a U-shaped distribution pattern of incidence of 30-day postoperative major cardiac events was observed, with the lowest risk in the overweight group. When using the normal-weight group as a reference, no difference was found in either the obesity or overweight groups in terms of a major cardiac adverse event (MACE). However, risk of a 30-day postoperative MACE was significantly higher in the underweight group (odds ratio [OR] 2.916, 95% confidence interval [CI]: 1.072–7.931, P = 0.036). CONCLUSION: Although not statistically significant, the U-shaped relation between BMI and cardiac complications indicates the obesity paradox possibly exists.